Consumer Expenditure Survey, 2006: Interview Survey and Detailed Expenditure Files ([Verlag nicht ermittelbar], 2008)
The ongoing Consumer Expenditure Survey (CES) provides a continuous flow of information on the buying habits of American consumers and also furnishes data to support periodic revisions of the Consumer Price Index.